The Impact of Structural Reforms on Economic Growth in Turkey: Evidence from Linear and Nonlinear ARDL Modeling - Yalçinkaya, Omer; Daştan, Muhammet; Karabulut, Kerem (Estudios de Economía, 2021)
This paper investigates the relationship between structural reforms and economic growth in Turkey during the 1990-2019 period. Employing a novel database (the MONA database), it constructs structural reform indexes for the fiscal, financial, real, and trade sectors with two different approaches (z-score and min-max). The study uses both the linear ARDL and nonlinear ARDL (NARDL) models to provide additional robust evidence of the response of economic growth to structural reforms. The findings indicate that financial, fiscal, real, and total structural reforms have positive and statistically significant effects on economic growth in Turkey, although the growth potential of trade structural reforms seems not to have been realized.